2019
DOI: 10.1021/acssuschemeng.9b06305
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic PLA-LCP Composites: A Route toward Sustainable, Reprocessable, and Recyclable Reinforced Materials

Abstract: Reprocessing of reinforced composites is generally accompanied by loss of value and performance, as normally the reinforcing phase is damaged, or the matrix is lost in the process. In the search for more sustainable recyclable composite materials, we identify blends based on poly( l -lactide) (PLA) and thermotropic liquid crystalline polymers (LCP) as highly promising self-reinforced thermoplastic composites that can be recycled several times without loss in mechanical properties. For ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…To maintain the mechanical performance upon reprocessing, the use of a higher viscosity PLLA matrix (in combination with CE-1:1 ) or a different LCP ( CE-3:2 with the same PLLA matrix) will be beneficial, as this prevents infeasible viscosity ratios upon reprocessing. 16 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain the mechanical performance upon reprocessing, the use of a higher viscosity PLLA matrix (in combination with CE-1:1 ) or a different LCP ( CE-3:2 with the same PLLA matrix) will be beneficial, as this prevents infeasible viscosity ratios upon reprocessing. 16 …”
Section: Resultsmentioning
confidence: 99%
“… 14 , 15 For an LCP-PLA composite, we have demonstrated that the morphology and mechanical performance remain constant irrespective of the number of reprocessing cycles, given that the viscosity of the dispersed LCP phase remains lower than that of the PLA matrix (i.e., viscosity ratio < 1). 16 …”
Section: Introductionmentioning
confidence: 99%
“…The final material is usually non‐porous. PLA can be processed by HME alone or with the addition of other polymers as well as different organic and inorganic substances 72–84 . When the molten PLA is extruded through a sheet die and quenched on polished chrome rollers that are cooled with circulating water, PLA films (usual thickness 0.076 mm) and sheets (usual thickness 0.25 mm) are produced 23 .…”
Section: Methods For Pla Processingmentioning
confidence: 99%
“…Many studies have shown that the phase morphology of TPV has a considerable effect on PLA toughening. 12,36,38 Therefore, in order to remove the PLA phase, dichloromethane was used to etch the cryo-fractured surface of the PLA/ENR/SiO 2 /KH550 TPVs, and then SEM was employed to study the effect of KH550 on the morphology of ENR phase in the TPVs. According to our previous report, ENR owned a higher melt strength than PLA melts, and a certain volume percentage of ENR could sustain a good continuous during the dynamic vulcanization, which resulted in the formation of a special co-continuous phase structure.…”
Section: Phase Morphologymentioning
confidence: 99%
“…Renewable resources have drawn increasing concerns for decades in consideration of environmental pollution and energy crises. [1][2][3][4] As a biodegradable polyester derived completely from biomass materials such as corns and potatoes, polylactic acid (PLA) exhibits excellent biocompatibility, [5][6][7] high mechanical strength, 8,9 and good recyclability, [10][11][12] which shows an enormous potential in alternative candidate for petroleum-based plastics. However, the inherent brittleness is one of the major barriers that hinder the widespread application of PLA.…”
Section: Introductionmentioning
confidence: 99%